Deep learning and its applications for vehicle networks - Hu, Fei; Rasheed, Iftikhar (CRC Press, Taylor & Francis Group, 2023)
This book is based on the work from world-famous experts on the application of DL for vehicle networks. It consists of the following five parts: 1. DL for vehicle safety and security, 2. DL for effective vehicle communications, 3. DL for vehicle control, 4. DL for information management, 5. Other applications
Description based on publisher supplied metadata and other sources